Blended Learning Approach with ADHD on Students (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This article explores the blended learning approach and its impact on students with Attention Deficit Hyperactivity Disorder (ADHD). By integrating traditional classroom methods with online learning components, this model aims to provide a flexible and engaging educational experience tailored to the unique needs of students with ADHD. The article highlights the benefits of blended learning, including personalized instruction, increased engagement, improved social skills, and enhanced critical thinking. Strategies for effective implementation are discussed, alongside potential challenges. The findings suggest that blended learning can significantly support the academic and social development of students with ADHD, ultimately fostering their success in educational settings.